Analysis of the Selection of Land Transportation Modes in Serang City - Fahrizal, Irfan; Dwiatmoko, Hermanto (ASTONJADRO, 2023)
The role of urban transportation is vast in supporting the mobility of city residents because, after all, urban people need city transportation, and most community groups depend on city transportation to meet their mobility needs. Along with the development of the era of online application-based transit, they are becoming newcomers as a service that makes it easier for people to carry out travel mobility, such as online motorcycle taxis. This study aims to determine the mode selection model between city transportation and online motorcycle in Serang City. The research approach is quantitative, with primary data sources obtained from distributing closed questionnaires to 43 city transportation travelers and 57 respondents to online motorcycle drivers. The data analysis used is the difference binomial logit model to determine the probability model of the traveler in choosing the mode. The results of modeling the choice of the way with the difference in binomial logit results in city transportation having the opportunity/probability of being chosen by travelers in Serang City at 45.64% while the probability/chance of selecting an online motorcycle is 54.36%.